Reading habits of Croatian adult library users during COVID-19 lockdown in 2020 - Petr Balog, Kornelija; Badurina, Boris; Lukačević, Srđan; Radmilović, Dino (Information Research an international electronic journal, 2022)
Introduction. COVID-19 outbreak in 2020 and consequent lockdown caused a number of changes in the everyday activities and lives of people globally. This paper looks into the change of reading habits of adult library users in Croatia. Method. The online survey was administered through social media and mailing lists of Croatian public libraries, but part of the sample was obtained through snowball technique. The research was carried out in the period of February 15th to March 1st, 2021 resulting with the sample of 1.463 adult library users. Analysis. The results were analysed by the SPSS statistical package utilising descriptive and inferential statistical methods (Chi-square, Spearman’s rank-order correlation coefficient). Results. Results show that almost 50.0% of the sample experienced the change of reading habits (particularly reading books) during the 2020 lockdown and every third respondent believed that they started spending more time reading in 2020. The younger the respondents, the more likely they were to have their reading habits affected by the 2020 lockdown. Conclusions. The prolonged state of a pandemic requires continuous study of reading habits that keep changing and evolving. Sex and age differences detected in the sample should be taken into account by those who create reading policies or offer services that promote reading.